2006
DOI: 10.1186/1465-9921-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Lung fibroblasts from patients with emphysema show markers of senescence in vitro

Abstract: Background: The loss of alveolar walls is a hallmark of emphysema. As fibroblasts play an important role in the maintenance of alveolar structure, a change in fibroblast phenotype could be involved in the pathogenesis of this disease. In a previous study we found a reduced in vitro proliferation rate and number of population doublings of parenchymal lung fibroblasts from patients with emphysema and we hypothesized that these findings could be related to a premature cellular aging of these cells. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 35 publications
3
113
1
2
Order By: Relevance
“…Levels of staining were much lower than in parenchymal lung fibroblasts. In accordance with our previous results (Müller et al 2006), staining in lung fibroblasts was more pronounced in patients with moderate to severe emphysema as compared to the control group, suggesting that a senescent phenotype is limited to lung fibroblasts in patients with emphysema. Both doubling time and β-gal staining were significantly increased in emphysema but did not correlate with each other.…”
Section: Accepted Manuscriptsupporting
confidence: 80%
See 3 more Smart Citations
“…Levels of staining were much lower than in parenchymal lung fibroblasts. In accordance with our previous results (Müller et al 2006), staining in lung fibroblasts was more pronounced in patients with moderate to severe emphysema as compared to the control group, suggesting that a senescent phenotype is limited to lung fibroblasts in patients with emphysema. Both doubling time and β-gal staining were significantly increased in emphysema but did not correlate with each other.…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…In addition, we found an increased staining for senescence-associated beta-galactosidase (β-gal, (Dimri et al 1995)), as well as increased mRNA expression of the insulin-like growth factor-binding proteins (IGFBP)-3 and -rP1 in these cells (Müller et al 2006). Both proteins have been shown earlier to be senescenceassociated (Goldstein et al 1991;Swisshelm et al 1995;Wilson et al 2002).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, our study design did not allow us to take into account the known heterogeneity of COPD and asthma phenotypes. These entities may have different impacts on telomere length or may trigger premature ageing processes via telomere-independent mechanisms, as reported for fibroblasts of patients with lung emphysema [45]. Unlike in clinical studies, diagnosis of COPD and asthma had to rely mainly on self-reported physician diagnosis, which certainly adds some potential for misclassification error.…”
Section: Discussionmentioning
confidence: 97%